Photoproduction of low-pT J/[psi] from peripheral to central Pb-Pb collisions at 5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Nath, Abhishek; et al. (Physics letters, 2023)
An excess of J/ψ yield at very low transverse momentum (pT<0.3 GeV/c), originating from coherent photoproduction, is observed in peripheral and semicentral hadronic Pb-Pb collisions at a center-of-mass energy per nucleon pair of sNN=5.02 TeV. The measurement is performed with the ALICE detector via the dimuon decay channel at forward rapidity (2.5<y<4). The nuclear modification factor at very low pT and the coherent photoproduction cross section are measured as a function of centrality down to the 10% most central collisions. These results extend the previous study at sNN=2.76 TeV, confirming the clear excess over hadronic production in the pT range 0−0.3 GeV/c and the centrality range 70-90%, and establishing an excess with a significance greater than 5σ also in the 50-70% and 30-50% centrality ranges. The results are compared with earlier measurements at sNN=2.76 TeV and with different theoretical predictions aiming at describing how coherent photoproduction occurs in hadronic interactions with nuclear overlap.
Online verfügbar: 17. September 2023, Artikelversion: 3. Oktober 2023
Im Titel ist der Buchstabe "T" tiefgestellt
*ALICE collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, J. Kim, M. Kim, M. Kroesen, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. Van Veen, M. Völkl, B. Windelbrand, A. Yuncu, F. Zanone [und 1009 weitere Personen]
Gesehen am 04.07.2025